A review on PLA-based biodegradable materials for biomedical applications - Muzamil Hussain; Shahzad Maqsood Khan; Muhammad Shafiq; Naseem Abbas (Giant, 2024)
Polylactic Acid (PLA) is a biodegradable polymer gaining popularity as a replacement for conventional plastics in different industrial sectors. However, PLA has inherent limitations and requires modifications to enhance its performance. This review article covers the different important aspects related to the PLA such as the synthesis route of PLA, biodegradation mechanism of PLA, properties of PLA, and applications of PLA in different sectors. The main focus of this review is to identify the different innovative copolymers, blends and composites of PLA for biomedical applications. Most important characteristics such as degradation behavior, biocompatibility and mechanical properties of these PLA-based biodegradable polymers were briefly discussed. This review indicates that the optimization of processing techniques and suitable selection of additives play an important role to achieve the desired properties of PLA. This review also discusses the issues associated to PLA-based materials for biomedical applications.